2015
DOI: 10.1097/ijg.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraocular Pressure Measurements Obtained by Icare PRO Rebound Tonometer, Tomey FT-1000 Noncontact Tonometer, and Goldmann Applanation Tonometer in Healthy Subjects

Abstract: The IOP readings with the new Icare PRO RT showed good correlation with those obtained by GAT. Tomey FT-1000 NCT underestimated the IOP compared with GAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
(39 reference statements)
4
7
1
Order By: Relevance
“…NCT seemed to be influenced the most by CCT (r 2 = 0.164, P < 0.000), followed by iCare pro (r 2 = 0.129, P < 0.000) and GAT (r 2 = 0.103, P < 0.000). In previous studies, Guler et al and Kato et al also reported similar positive correlations between IOP measured by NCT, iCare pro and GAT with CCT [9, 39]. As estimated by a regression equation, every 10 μm increase in CCT resulted in an increase in IOP as 0.6 mmHg with NCT, 0.5 mmHg in iCare pro, and 0.3 mmHg in GAT in normal IOP group.…”
Section: Discussionsupporting
confidence: 52%
“…NCT seemed to be influenced the most by CCT (r 2 = 0.164, P < 0.000), followed by iCare pro (r 2 = 0.129, P < 0.000) and GAT (r 2 = 0.103, P < 0.000). In previous studies, Guler et al and Kato et al also reported similar positive correlations between IOP measured by NCT, iCare pro and GAT with CCT [9, 39]. As estimated by a regression equation, every 10 μm increase in CCT resulted in an increase in IOP as 0.6 mmHg with NCT, 0.5 mmHg in iCare pro, and 0.3 mmHg in GAT in normal IOP group.…”
Section: Discussionsupporting
confidence: 52%
“…Rebound tonometry represents the most recent addition to this field, with results from healthy human adults reported to be in good agreement with those from Goldmann applanation tonometry, 30,31 and those from children being only slightly higher. 32,33 Rebound tonometers specifically designed for animal use, for example, in veterinary practice and research, are also now available.…”
mentioning
confidence: 64%
“…Icare PRO gives a mean IOP closer to that obtained with GAT. Previous reports showed that the mean IOP difference between Icare PRO and GAT was −0.38 mmHg (95% LOA was unclear), 27 −0.22 mmHg (95% LOA was between −2.8 and 2.4 mmHg), 28 0.01±2.16 mmHg (95% LOA was between −4.22 and 4.25 mmHg), 10 0.1 mmHg (95% LOA was between −3.6 and 3.8 mmHg), 29 and 0.43±2.28 mmHg (95% LOA was between −4.04 and 4.90 mmHg). 4 …”
Section: The Characteristics Of Each Device and Iop Valuesmentioning
confidence: 93%